Can we be the masters of our minds? / Emily Jothee Mathai - Mathai, Emily Jothee (Academy of Language Studies, 2022)
Mind is the most powerful possession of an individual. It can make you or break you miserably. Controlling one’s mind is crucial towards controlling oneself. Sounds easy, doesn’t it? Well, easy when met with simple obstacles in life but in difficult situations, the mind could go on a roller coaster and without realization - you may lose control of yourself. Our brain is likened to a rubber band. It can be stretched to a certain limit. If overstretched beyond its limitation, it snaps and there goes an erupted band. On a similar note, if you drain your brain round the clock (worrying about something), it will snap and lose the ability to take control of your body - if you know what I mean!